Trees as Level Sets for Pseudoharmonic Functions in the Plane - Polulyakh, E. O. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let T be a finite or infinite tree and let V 0 be the set of all vertices of T of valency 1. We propose a sufficient condition for the image of the imbedding ψ: T \V 0 → \( {{\mathbb{R}}^2} \) to be a level set of a pseudoharmonic function.